AS CONSEQUÊNCIAS DA RADIAÇÃO SOLAR EM MULHERES AGRICULTORAS - Heck, Maira; Eickhoff, Heloísa M.; Ribeiro, Mônica; Castro, Kátia; Janine A. C. C. D. S.,; Cadore, Janine A. (Salão do Conhecimento, 2013)
Resumo